Terpenoids from a multiple shoot culture of Telekia speciosa - Anna Stojakowska; Janusz Malarz; Wanda Kisiel (Acta Societatis Botanicorum Poloniae, 2011)
Multiple shoots of Telekia speciosa were cultivated on MS medium containing 4.44 µM BAP and 0.54 µM NAA, solidified with agar. After eight weeks of culture the shoots were harvested and extracted with methanol. From the methanol extract one pseudoguaianolide – 2,3-dihydroaromaticin and three thymol derivatives: 8-hydroxy-9,10-diisobutyryloxythymol, 10-isobutyryloxy-8,9-epoxythymyl isobutyrate and 10-(2-methylbutyryloxy)-8,9-epoxythymyl isobutyrate were isolated as major secondary metabolites. Moreover, the shoots produced megastigmane and monoterpene glucosides, which were isolated for the first time from the species. The content of 2,3-dihydroaromaticin in the shoot culture was similar to that found in the intact plant, whereas yields of the three thymol derivatives were higher from multiple shoots than from the plants grown in the open field.